Ultra-fast and universal detection of Gram-negative bacteria in complex samples based on colistin derivatives. (22nd January 2020) - Ryu, Jea Sung; Im, San Hae; Kang, Yoo Kyung; Kim, Yang Soo; Chung, Hyun Jung
Abstract : A rapid and universal assay for detection of Gram-negative bacteria was developed using a fluorescent derivative of colistin. Labeling is achieved within 10 min in various bacteria relevant to hospital-acquired infections in complex samples. Abstract : Gram-negative bacteria are a significant cause of infections acquired in both hospital and community settings, resulting in a high mortality rate worldwide. Currently, a Gram-negative infection is diagnosed by symptom evaluation and is treated with empiric antibiotics which target both Gram-negative and Gram-positive bacteria. A rapid and simple diagnostic method would enable immediate and targeted treatment, while dramatically reducing antibiotic overuse. Herein, we introduce a method utilizing a fluorescent derivative of colistin (COL-FL), that can directly label the Gram-negative cell wall of live bacteria and universally detect the targets within 10 min. By using the COL-FL assay, we achieved the differential labeling of various Gram-negative pathogens related to hospital-acquired infections, which could be subsequently detected via spectrofluorometry and microscopy. Further, we determined that our method can be used for complex samples, such as combinations of multiple bacterial types; bacteria in the presence of mammalian cells; and bacteria with serum components. This assay can be integrated into a simple diagnostic platform for rapid screening tests and the stratification of Gram-negative bacterial infections in the clinic.